A New Method for Ethical and Efficient Evidence Generation for Off-Label Medication Use in Oncology (A Case Study in Glioblastoma) - Agrawal, Samir; Vamadevan, Padman; Mazibuko, Ndaba; Bannister, Robin; Swery, Raphael; Wilson, Shanna; Edwards, Sarah (Frontiers in Pharmacology, 2019)
In oncology, pre-clinical and early clinical data increasingly support the use of a number of candidate “non-cancer” drugs in an off label setting against multiple tumor types. In particular, metabolically targeted drugs show promise as adjuvant chemo and radio sensitizers, improving or restoring sensitivity to standard therapies. The time has come for large scale clinical studies of off-label drugs in this context. However, it is well recognized that high-cost randomized controlled trials may not be an economically viable option for studying patent-expired off label drugs. In some cases, randomized trials could also be considered as ethically controversial. This perspective article presents a novel approach to generating additional clinical data of sufficient quality to support changes in clinical practice and re-labelling of such drugs for use in oncology. Here we suggest that a pluralistic evidence base and triangulation of evidence can support clinical trial data for off label drug use in oncology. An example of an off-label drug protocol brought to the clinic for glioblastoma patients is presented, along with preliminary retrospective data from the METRICS study (NCT02201381). METRICS is a novel participant-funded, open-label, non-randomized, single-arm real-world study designed to gather high quality evidence on the safety, tolerability and effectiveness of four off-label metabolically targeted medicines as an adjunctive cancer treatment for glioblastoma patients.